2016
DOI: 10.1039/c6cp01587e
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of binary gas adsorption in nanopores

Abstract: MCM-41 nanoporous silicas show a very high selectivity for monoalcohols over aprotic molecules during adsorption of a binary mixture in the gas phase. We present here an original use of gravimetric vapour sorption isotherms to characterize the role played by the alcohol hydrogen-bonding network in the adsorption process. Beyond simple selectivity, vapour sorption isotherms measured for various compositions help to completely unravel at the molecular level the step by step adsorption mechanism of the binary sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Figure 2 shows that the predicted adsorption isotherms are in fair agreement with those obtained from experiments. 31 Interestingly, Fig. 2 exhibits that the capillary condensation pressure is qualitatively reproduced for both TOL and TBA components.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Figure 2 shows that the predicted adsorption isotherms are in fair agreement with those obtained from experiments. 31 Interestingly, Fig. 2 exhibits that the capillary condensation pressure is qualitatively reproduced for both TOL and TBA components.…”
Section: Resultsmentioning
confidence: 85%
“…Whereas these effects have been largely investigated in the case of confined single components [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and immiscible binary mixtures, [28][29][30] less works have been devoted to the confinement of miscible liquid mixtures. 15,[31][32][33] Recently, Muthulakshmi et al 34 reported an experimental evidence of a partial phase separation of an ethanol-water mixture confined in mesoporous silica using positron annihilation lifetime spectroscopy. They showed that a small fraction of the ethanol molecules seemed to be anchored at the silica surface.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations